2021
DOI: 10.3389/fimmu.2021.627650
|View full text |Cite
|
Sign up to set email alerts
|

Association of Isocitrate Dehydrogenase (IDH) Status With Edema to Tumor Ratio and Its Correlation With Immune Infiltration in Glioblastoma

Abstract: PurposeThe extent of preoperative peritumoral edema in glioblastoma (GBM) has been negatively correlated with patient outcome. As several ongoing studies are investigating T-cell based immunotherapy in GBM, we conducted this study to assess whether peritumoral edema with potentially increased intracranial pressure, disrupted tissue homeostasis and reduced local blood flow has influence on immune infiltration and affects survival.MethodsA volumetric analysis of preoperative imaging (gadolinium enhanced T1 weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
4
1
0
Order By: Relevance
“…suggested that IDH wild-type glioblastomas have a high peritumoral edema volume/tumor volume (E/T) ratio [13]. The results of this study based on quantitative evaluation of edema are consistent with this finding.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…suggested that IDH wild-type glioblastomas have a high peritumoral edema volume/tumor volume (E/T) ratio [13]. The results of this study based on quantitative evaluation of edema are consistent with this finding.…”
Section: Discussionsupporting
confidence: 87%
“…However, there are few quantitative studies of peritumoral edema in gliomas with an IDH mutation. Dubinski et al suggested that IDH wild-type glioblastomas have a high peritumoral edema volume/tumor volume (E/T) ratio [ 13 ]. The results of this study based on quantitative evaluation of edema are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…For additional comparison of the main rCBV variables, an additional figure of dispersion graphics is also provided in Supplementary Material 3. cases, they may more closely align with pure edema. Indeed, this hypothesis aligns well with prior knowledge: Glioblastomas are known to generate more pronounced edema, whereas Astrocytomas manifest a more substantial proportion of non-enhancing tumor tissue in the T2-FLAIR abnormality [25].…”
Section: Discussionsupporting
confidence: 86%
“…Such regions may represent a greater degree of coexisting very-low vascularized infiltrated tissue in IDH-mutant cases, while in IDH-wildtype cases, they may more closely align with pure edema. Indeed, this hypothesis aligns well with prior knowledge: Glioblastomas are known to generate more pronounced edema, whereas Astrocytomas manifest a more substantial proportion of non-enhancing tumor tissue in the T2-FLAIR abnormality [ 25 ].…”
Section: Discussionsupporting
confidence: 83%
“…Finally, we suggested that Habitat 8, due to its reduced diffusivity, might identify areas of tumor infiltration beyond the CE vital core, while Habitat 7 areas of vasogenic edema (with no, or less prominent, tumor infiltration). Interestingly, in our series, the relative volume of pure edema (Habitat 7) was significantly higher in IDH-1 wild-type tumors, compared to IDH-1 mutated lesions, similarly to other recent studies (Dubinski et al, 2021).…”
Section: Combined Pet and Mri Hypoxia Perfusion And Diffusion Spatial...supporting
confidence: 92%